RIGHT TO THE GENETIC IDENTITY OF THE CHILD X RIGHT TO PRESERVE THE IDENTITY OF THE GAMETHER DONOR - GonçalvesTavares, Gabriela; de Paula Ferreira, Larissa; Veggi Moreira, Raquel; Lacerda Tinoco Boechat Cabral, Hildeliza; Medeiros de Souza, Carlos Henrique (LINKSCIENCEPLACE, 2026)
Currently, before the incessant progress of social transformation, the Brazilian family legal order is gradually lacking of new reflections on the familiar structuring. By means of a qualitative methodology, the present work is based on works, scientific articles by experts in the subject, as well as on current and relevant legal provisions in order to examine questions about the right to genetic origin, its integration to the rights of the personality, as well as the right to membership and, consequently, to paternity investigation. Identifying the genetic origin consists of a very personal right and is detached from the recognition of the state of affiliation. Considering, in any case, the best interest of the child and the affection to declare paternity and son ship, it is concluded that hindering the right to the conscience of genetic origin, also damages the right to the dignity of the human person.